Repairing TALEN-mediated double-strand break by microhomology-mediated recombination in tobacco plastids generates abundant subgenomic DNA. (December 2021) - Huang, Chih-Hao; Liu, Yu-Chang; Shen, Jia-Yi; Lu, Fu-I; Shaw, Shyh-Yu; Huang, Hao-Jen; Chang, Ching-Chun
Highlights: TALEN technology was reported to edit plastid DNA in transgenic tobacco. Tobacco with overexpression of TALEN show the instability of plastid genome. Repairing of damaged plastid DNA result in point mutation, deletion and inversion. Transgenic plants exhibit various degrees of chlorotic phenotype. Microhomology-mediated recombination generate abundant subgenomic DNA. Abstract: Transcription activator-like effector nuclease (TALEN) technology has been widely used to edit nuclear genomes in plants but rarely for editing organellar genomes. In addition, ciprofloxacin, commonly used to cause the double-strand break of organellar DNA for studying the repair mechanism in plants, confers no organellar selectivity and site-specificity. To demonstrate the feasibility of TALEN-mediated chloroplast DNA editing and to use it for studying the repair mechanism in plastids, we developed a TALEN-mediated editing technology fused with chloroplast transit peptide (cpTALEN) to site-specifically edit the rpoB gene via Agrobacteria-mediated transformation of tobacco leaf. Transgenic plants showed various degrees of chlorotic phenotype. Repairing damaged plastid DNA resulted in point mutation, large deletion and small inversion surrounding the rpoB gene by homologous recombination and/or microhomology-mediated recombination. In an albino line, microhomology-mediated recombination via a pair of 12-bp direct repeats between rpoC2 and ycf2 genes generated the chimeric ycf2-rpoC2 subgenome, with the level about 3- to 5-fold higher for subgenomic DNA than ycf2 . Additionally, the expression of chimeric ycf2-rpoC2 transcripts versus ycf2 mRNA agreed well with the level of corresponding DNA. The ycf2-rpoC2 subgenomic DNA might independently and preferentially replicate in plastids.